2021
DOI: 10.1021/acs.jpca.1c08037
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Water Uptake of Individual Marine and Biologically Relevant Atmospheric Particles Using Micro-Raman Spectroscopy

Abstract: The interaction of water vapor and the water uptake behavior of atmospheric particles are often investigated as a function of relative humidity (0−100% RH) at ambient temperature. However, lower temperature studies are important to understand how atmospheric particles nucleate ice through various mechanisms including immersion freezing. Immersion freezing requires the formation of a condensed water droplet at lower temperatures prior to freezing. To better understand low-temperature water uptake behavior of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This finding supports the core–shell morphology to a limited extent; in addition to saturating the surface, organics, and specifically BCL, also accumulate in the center of the particle. Mael et al recently observed this phenomenon during water uptake experiments: neither complete phase separation nor full dissolution occurs in the case of some organics, leading to the formation of inclusions . Additionally, Huang et al observed that organic aerosols with an organic component containing an O:C ratio <0.8 exhibited phase coexistence .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the core–shell morphology to a limited extent; in addition to saturating the surface, organics, and specifically BCL, also accumulate in the center of the particle. Mael et al recently observed this phenomenon during water uptake experiments: neither complete phase separation nor full dissolution occurs in the case of some organics, leading to the formation of inclusions . Additionally, Huang et al observed that organic aerosols with an organic component containing an O:C ratio <0.8 exhibited phase coexistence .…”
Section: Resultsmentioning
confidence: 99%
“…Mael et al recently observed this phenomenon during water uptake experiments: neither complete phase separation nor full dissolution occurs in the case of some organics, leading to the formation of inclusions. 121 Additionally, Huang et al observed that organic aerosols with an organic component containing an O:C ratio <0.8 exhibited phase coexistence. 32 The O:C ratios of our SSA models align well with this observation (Table S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Advances in single particle techniques allow quantitative measurements of hygroscopic growth factors for individual aerosol particles. 240,241 Estillore et al 242 and Lee et al 243 used AFM to study water uptake on SSA particles with a core-shell morphology. They generated these particles in a wave ume with seawater collected off the coast of California, with an induced phytoplankton bloom.…”
Section: Hygroscopicitymentioning
confidence: 99%
“…Liang et al: Single-particle Raman spectroscopy ics, and their mixtures (Chu et al, 2015;Laskina et al, 2015;W. Wang et al, 2021;Tobon et al, 2021;Ashraf et al, 2021), as well as mineral dust (Liu et al, 2008), secondary organic aerosols (Wu et al, 2020), and atmospherically relevant biological macromolecules (Mael et al, 2021), using single-particle Raman spectroscopy. It should be noted that evaporation of some components and precipitation of some salts could occur during the RH cycling in hygroscopicity measurements (Li et al, 2017(Li et al, , 2021Cai and Zhao, 2018;Ma et al, 2019a, b;Wu et al, 2020).…”
Section: Hygroscopicity and Phase Transitionmentioning
confidence: 99%